Meningkatkan Ekspresi Emosi dan Pengendalian Diri Anak Melalui Media Balok di TK Ukan Hasupa Samarinda - Rahma, Aulia Nur; Feliana, Melati; Musarofah, Musarofah; Safitri, Dewi; Fadhilah, Alfi Nur; Erawati, Henni; Jumaiyah, Jumaiyah (Faculty of Education and Teacher Training of UINSI Samarinda, 2025)
The development of emotions and self-regulation is a crucial aspect of early childhood growth. This study aims to examine the effectiveness of block play as a learning medium to enhance the social-emotional skills of children at Ukan Hasupa Kindergarten. Utilizing a Classroom Action Research (CAR) approach, the study involved 17 children aged 5-6 years. Pre-cycle results indicated that children's social-emotional skills were at a level of 12%, with difficulties in emotional expression and self-regulation. Following the implementation of block play, these skills significantly increased to 81% in the first cycle. This research emphasizes the importance of effective interventions to support children's social-emotional development, enabling them to adapt well in social and academic environments.